Hormonal and metabolic responses across phases of combined oral contraceptive use and menstrual cycle in young elite female athletes - Collomp, K.; Olivier, A.; Teulier, C.; Bonnigal, J.; Crépin, N.; Buisson, C.; Ericsson, M.; Duron, E.; Favory, E.; Zimmermann, M.; Amiot, V.; Castanier, C. (European Journal of Applied Physiology, 2025)
Purpose Despite the significant number of female athletes using combined oral contraceptives (COCs), there is scant literature on their hormonal and metabolic effects across different phases.